PENGUATAN KOMPETENSI GURU SD DALAM PENYUSUNAN BAHAN AJAR DIGITAL DAN MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI - Gagaramusu, Yusdin; Ramadhani, Sriyati; Herlina, Herlina; Purnamasari, Danti Indriastuti; Guci, Ammar Abdullah Joni (Jurnal Abdi Insani, 2026)
The use of technology in education is increasingly becoming a crucial need in today's digital era. However, many elementary school teachers have not yet fully utilized digital teaching materials and technology-based learning media. Therefore, this community service program aims to strengthen elementary school teachers' competencies in developing digital teaching materials and technology-based learning media. The most appropriate method for the program Strengthening Elementary School Teacher Competence in Developing Digital Teaching Materials and Technology-Based Learning Media is a practice-based training method integrated with ongoing mentoring. This activity includes socialization, training, Technology Implementation, Mentoring and Evaluation of Activities and Program Sustainability. Basic understanding of the use of technology in learning, training in creating interactive learning media, and developing digital teaching materials that align with curriculum requirements are provided. The results of this community service program demonstrate an increase in teachers' ability to utilize technology as an effective learning tool. Teachers are able to develop digital teaching materials that are engaging and easy for students to understand, and utilize technology-based learning media to support a more creative and innovative learning process. These results have significant significance in improving the quality of elementary education by strengthening teachers' abilities in the appropriate use of technology. Thus, strengthening teacher competency in this field will contribute to improving the quality of education at the elementary school level.